The Cambridge world history. Volume 6, The construction of a global world, 1400-1800 CE. Part2, Patterns of change - Bentley, Jerry H., 1949-; Subrahmanyam, Sanjay; Wiesner, Merry E., 1952- (Cambridge : Cambridge University Press, 2015)
The era from 1400 to 1800 saw intense biological, commercial, and cultural exchanges, and the creation of global connections on an unprecedented scale. Divided into two books, Volume 6 of The Cambridge World History considers these critical transformations. The first book examines the material and political foundations of the era, including global considerations of the environment, disease, technology, and cities, along with regional studies of empires in the eastern and western hemispheres, crossroads areas such as the Indian Ocean, Central Asia, and the Caribbean, and sites of competition and conflict, including Southeast Asia, Africa, and the Mediterranean. The second book focuses on patterns of change, examining the expansion of Christianity and Islam, migrations, warfare, and other topics on a global scale, and offering insightful detailed analyses of the Columbian exchange, slavery, silver, trade, entrepreneurs, Asian religions, legal encounters, plantation economies, early industrialism, and the writing of history.
Part 2, Patterns of change. 1. Global migrations / Dirk Hoerder -- 2. Patterns of warfare, 1400-1800 / Jeremy Black -- 3. The first global dialogues : inter-cultural relations, 1400-1800 / John E. Wills, Jr. -- 4. Legal encounters and the origins of global law / Lauren Benton and Adam Clulow -- 5. The Columbian exchange / Noble David Cook -- 6. The slave trade and the African diaspora / John Thornton -- 7. The organization of trade in Europe and Asia, 1400-1800 / Francesca Trivellato -- 8. Entrepreneurs, families and companies / Charles H. Parker -- 9. Silver in global context, 1400-1800 / Dennis O. Flynn -- 10. Dutch and English trade to the east : the Indian Ocean and the Levant, to about 1700 / James D. Tracy -- 11. Plantation societies / Trevor Burnard -- 12. Industrious revolutions in early modern world history / Kaoru Sugihara and R. Bin Wong -- 13. The scholarly discovery of religion in early modern times / Guy Stroumsa -- 14. Christianity in Europe and overseas / R. Po-Chia Hsia -- 15. Islam in the early modern world / Nile Greene -- 16. Religious change in East Asia / Eugenio Menegon and Gina Cogan -- 17. On early modern historiography / Sanjay Subrahmanyam -- 18. Microhistory and world history / Carlo Ginzburg.
Title from publisher's bibliographic system (viewed on 15 Jan 2016).
Keywords: History, Modern; World history